Growth arrest and DNA damage-inducible 45: a new player on inflammatory diseases - Ma, Yanmei; Hossen, Md Munnaf; Huang, Jennifer Jin; Yin, Zhihua; Du, Jing; Ye, Zhizhong; Zeng, Miaoyu; Huang, Zhong (Frontiers in Immunology, 2025)
Growth arrest and DNA damage-inducible 45 (GADD45) proteins are critical stress sensors rapidly induced in response to genotoxic/physiological stress and regulate many cellular functions. Even though the primary function of the proteins is to block the cell cycle, inhibit cell proliferation, promote cell apoptosis, and repair DNA damage to cope with the damage caused by internal and external stress on the body, evidence has shown that GADD45 also has the function to modulate innate and adaptive immunity and plays a broader role in inflammatory and autoimmune diseases. In this review, we focus on the immunomodulatory role of GADD45 in inflammatory and autoimmune diseases. First, we describe the regulatory factors that affect the expression of GADD45. Then, we introduce its immunoregulatory roles on immune cells and the critical signaling pathways mediated by GADD45. Finally, we discuss its immunomodulatory effects in various inflammatory and autoimmune diseases.